Myth and identity in the epic of Imperial Spain - Davis, Elizabeth B. (University of Missouri Press, 2000)
The first in-depth analysis of some of the most important epic poems of the Spanish Golden Age, Myth and Identity in the Epic of Imperial Spain breathes new life into five of these long- neglected texts. Elizabeth Davis demonstrates that the epic must not be overlooked, for doing so creates a significant gap in one's ability to appraise not only the cultural practice of the imperial age, but also the purest expression of its ideology. Davis's study focuses on heroic poetry written from 1569 to 1611, including Alonso de Ercilla's La Araucana, undeniably the most significant epic poem of its time. Also included are Diego de Hojeda's La Christiada, Juan Rufo's La Austriada, . Lope de Vega's Jerusalén Conquistada, and Cristóbal de Virués's Historia del Monserrate. Examining these epics as the major site for the construction of cultural identities and Renaissance nationalist myths, Davis analyzes the means by which the epic constructs a Spanish sense of self. Because this sense of identity is not easily susceptible to direct representation, it is often derived in opposition to an "other," which serves to reaffirm Spanish cultural superiority. The Spanish Christian caballeros are almost always pitted against Amerindians, Muslims, Jews, or other adversaries portrayed as backward or heathen for their cultural and ethnic differences. The pro-Castilian elite of sixteenth-century Spain faced the daunting task of constructing unity at home in the process of expansion and conquest abroad, yet ethnic and regional differences in the Iberian Peninsula made the creation of an imperial identity particularly difficult. The epic, as Davis shows, strains to convey the overriding image of a Spain that appears more unified than the Spanish empire ever truly was. An important reexamination of the Golden Age canon, Myth and Identity in the Epic of Imperial Spain brings a new twist to the study of canon formation. While Davis does not ignore more traditional approaches to the literary text, she does apply recent theories, such as deconstruction and feminist criticism, to these poems, resulting in an innovative examination of the material. Confronting such issues as canonicity, gender, the relationship between literature and Golden Age culture, and that between art and power, this publication offers scholars a new perspective for assessing Golden Age and Transatlantic studies